ENVIRONMENTAL MANAGEMENT OF MINE WATER, CONSIDERING EUROPEAN WATER LEGISLATION. CASE STUDY OF MEGALOPOLIS MINES - Dimitrakopoulos, D.; Vassiliou, E.; Tsangaratos, P.; Ilia, I. (Bulletin of the Geological Society of Greece, 2010)
Mining activities causes many environmental problems to the surrounding areas, as other industrial activities do also. However mine water pollution, is considered a tough task to handle, as it requires specific regulations, quite distinct from those applicable to most other industrial processes. Even though there are several federal laws and regulations in Greece and in the European Union that influences the mining industry and mine water management, still certain factors complicates their implementation. The aim of this paper is to present a brief description of mining legislation in European Union and in Greece and also the efforts of Public Power Corporation (DEI), to integrate the Directive 2000/60/EC and Greek legislation in mining sector. The study is focused in Megalopolis open pit and in its surrounding, where lignite exploitation takes place and management of mine water is implemented. The outcomes of this effort are evaluated, considering the specific environmental conditions of the surrounding area and suggestions and methods, for mine water management, are proposed.